Evaluasi Sistem E-rapor Direktorat PSMA Terhadap Aspek Usability dan Utility (Studi Kasus: SMAN 1 Tuban) - Nada Awaliyah Mas'an Putri; Ismiarta Aknuranda; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
E-rapor Direktorat PSMA is a system provided by the Indonesian government to help process the scores of senior high school students. Every national school is required to use this system and due to there is still no structured research to find out how the system is used in school. In this research usability testing will be used to investigate wether the system is usable for teachers of SMAN 1 Tuban. System utility research was also conducted to explore the use of the system in this school and how the system fulfilled the school requirement. The test is conducted using usability testing method based on the three usability aspects as accordance to ISO 9241-11, namely effectiveness, efficiency, and satisfaction. The data was obtained from task testing, questionnaires, and interviews. The result of each usability aspects is calculated using relations formula to obtain a quantitative assessment, other than that, the testing also resulted in some specific problems with the improvement suggestions given. The utility research is conducted through interview based on the six utility aspects by Kendall & Kendall which consisted of possession, form, time, place, actualization, and goal. The result of utility research is in form of quantitative assessment of the system and some new user needs. The conclusion from this research is users can operate the system well but the system still needs some improvements in some aspects.